Upper Extremity Injuries in NASCAR Drivers and Pit Crew: An Epidemiological Study. Issue 2 (12th February 2016) - Wertman, Gary; Gaston, R. Glenn; Heisel, William
Background: Understanding the position-specific musculoskeletal forces placed on the body of athletes facilitates treatment, prevention, and return-to-play decisions. While position-specific injuries are well documented in most major sports, little is known about the epidemiology of position-specific injuries in National Association for Stock Car Automobile Racing (NASCAR) drivers and pit crew. Purpose: To investigate position-specific upper extremity injuries in NASCAR drivers and pit crew members. Study Design: Descriptive epidemiological study. Methods: A retrospective chart review was performed to assess position-specific injuries in NASCAR drivers and pit crew members. Included in the study were patients seen by a single institution between July 2003 and October 2014 with upper extremity injuries from race-related NASCAR events or practices. Charts were reviewed to identify the diagnosis, mechanism of injury, and position of each patient. Results: A total of 226 NASCAR team members were treated between July 2003 and October 2014. Of these, 118 injuries (52%) occurred during NASCAR racing events or practices. The majority of these injuries occurred in NASCAR changers (42%), followed by injuries in drivers (16%), carriers (14%), jack men (11%), fuel men (9%), and utility men (8%). The majority of the pit crew positions are at risk for epicondylitis, while drivers are most likely to experience neuropathies, such as hand-arm vibration syndrome. The changer sustains the most hand-related injuries (42%) on the pit crew team, while carriers commonly sustain injuries to their digits (29%). Conclusion: Orthopaedic injuries in NASCAR vary between positions. Injuries in NASCAR drivers and pit crew members are a consequence of the distinctive forces associated with each position throughout the course of the racing season. Understanding these forces and position-associated injuries is important for preventive measures and facilitates diagnosis and return-to-play decisions so that each team can function at its maximal efficiency.